Evaluation of the NHS England Low-Calorie Diet implementation pilot: a coproduced mixed-method study - Louisa J Ells; Tamara Brown; Jamie Matu; Ken Clare; Simon Rowlands; Maria Maynard; Karina Kinsella; Kevin Drew; Jordan R Marwood; Pooja Dhir; Tamla S Evans; Maria Bryant; et al. (Health and Social Care Delivery Research)
Background National Health Service England piloted a low-calorie diet programme, delivered through total diet replacement and behaviour change support via 1 : 1, group or digital delivery, to improve type 2 diabetes in adults with excess weight. Aim To coproduce a qualitative and economic evaluation of the National Health Service low-calorie diet pilot, integrated with National Health Service data to provide an enhanced understanding of the long-term cost-effectiveness, implementation, equity and transferability across broad and diverse populations. Research questions What are the theoretical principles, behaviour change components, content and mode of delivery of the programme, and is it delivered with fidelity to National Health Service specifications? What are the service provider, user and National Health Service staff experiences of the programme? Do sociodemographics influence programme access, uptake, compliance and success? What aspects of the service work and what do not work, for whom, in what context and why? Can the programme be improved to enhance patient experience and address inequities? What are the programme delivery costs, and policy implications for wide-spread adoption? Methods A mixed-methods study underpinned by a realist-informed approach was delivered across five work packages, involving: semistructured interviews with service users (n = 67), National Health Service staff (n = 55), service providers (n = 9); 13 service provider focus groups; and service user surveys (n = 719). Findings were triangulated with clinical data from the National Health Service England’s first cohort analysis (n = 7540). Results Fifty-five per cent of service users who started total diet replacement completed the programme and lost an average of 10.3 kg; 32% of those with data available to measure remission achieved it. Examination of programme mobilisation identified barriers around referral equality and the impact of COVID-19, while effective cross-stakeholder working and communication were key facilitators. Service delivery and fidelity assessments identified a drift in implementation fidelity, alongside variation in the behaviour change content across providers. Perceived barriers to programme uptake and engagement aligned across service providers and users, resulting in key learning on: the importance of person-centred care, service user support needs, improvements to total diet replacement and the social and cultural impact of the programme. Early National Health Service quantitative analyses suggest some socioeconomic variation in programme uptake, completion and outcomes. Insights from the evaluation and National Health Service data were combined to develop the programme theory and underpinning context, mechanisms and outcomes. These were used to develop a list of recommendations to improve the cultural competency of programme delivery, total diet replacement delivery, peer support and address psychological support needs. Cost-effectiveness analyses using short-term follow-up data indicated there is potential for the programme to be cost-effective, but not cost saving. Conclusions The National Health Service low-calorie diet can provide a clinically effective and potentially cost-effective programme to support weight loss and glycaemic control in adults with type 2 diabetes. However, this evaluation identified areas for improvement in referral equity, uptake and completion, and fidelity of delivery, which have informed the development of the programme, which has now been rolled out nationally. Ongoing programme monitoring and long-term follow-up are now required. Future work and limitations The real-world setting limited some data collection and analysis. Future work will focus on the analysis of long-term clinical and cost-effectiveness, and addressing inequalities. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR132075. Plain language summary What questions did this study answer? Did the National Health Service Low-Calorie Diet Programme help patients to lose weight and improve their diabetes? Was the programme delivered as the National Health Service intended? Who did the programme work and not work for, and why? What did patients and staff involved in the programme think about it? Did the programme provide value for money? How can the programme be improved for the future? What did we do? We asked staff involved, and looked at patients’ records to find out what worked and didn’t, for whom and why. All referred patients were invited to complete a short survey to ask for their views about the programme. We looked at the experiences of 67 patients from different backgrounds who took part in the programme. This involved talking to them and asking some of them to share photographs or video diaries that documented their journeys. We looked at how much the programme cost the National Health Service and any unintended patient costs, and whether it offered value for money. We spoke to different people to understand what could be improved. We found Some differences in the extent to which the programme was delivered as the National Health Service intended. Some people were more likely to start and complete the programme than others. The programme did help people to lose weight and improve their diabetes, but people who have had diabetes for longer, or from Asian or black ethnicities may not do as well. Generally, staff and patients spoke positively about the programme, but did highlight some areas that could be improved, for example providing planned pauses, a range of total diet replacement products, and more personalisation. The programme provided value-for-money. What happened next? Learning was used to improve the programme, which is now available across England.